PCB-Based Dual-Polarized Liquid Crystal Reflectarray With High Aperture Efficiency and Bridge-Shaped Biasing Topology for 2D Scanning - Hogyeom Kim; Byeongju Moon; Seungwoo Bang; Seongwoog Oh; Jungsuek Oh (IEEE Access)
This paper presents a novel dual-linearly polarized liquid crystal reflectarray antenna (DLP-LCRA) based on a printed circuit board (PCB) process. The proposed design employs a bridge-shaped biasing topology to reduce RF losses typically associated with bias lines in PCB-based implementations. While conventional DLP-LCRAs are often fabricated using glass substrates due to the difficulty of achieving sufficiently thin bias lines in PCB processes, this work demonstrates that a cost-effective and practical solution is possible through optimized biasing structures. The proposed reflectarray cell structure and biasing scheme enable wide 2D beam scanning with high aperture efficiency. Specifically, the bridge-shaped topology mitigates polarization-dependent RF losses and supports broad beam coverage in the E-, H-, and D-planes. The influence of the biasing layer is analyzed in detail using an equivalent circuit model for TE and TM modes. Experimental results validate the performance of the proposed DLP-LCRA, achieving a maximum aperture efficiency of 46.5 %, which represents a 106.67 % improvement over state-of-the-art designs.